2017
DOI: 10.1016/j.appet.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Academic stress and personality interact to increase the neural response to high-calorie food cues

Abstract: Psychosocial stress is associated with an increased intake of palatable foods and weight gain in stress-reactive individuals. Personality traits have been shown to predict stress-reactivity. However, it is not known if personality traits influence brain activity in regions implicated in appetite control during psychosocial stress. The current study assessed whether Gray's Behavioural Inhibition System (BIS) scale, a measure of stress-reactivity, was related to the activity of brain regions implicated in appeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 54 publications
1
20
0
3
Order By: Relevance
“…Nevertheless, some individuals might be more susceptible for the unhealthy choices due to certain psychological factors [ 44 ]. A recent study comparing students in the exam conditions versus the regular days, reported effects of stress on appetitive brain function [ 45 ]. Self-control was suggested to be affected by a personality trait which might cause overeating in susceptible subjects upon exposure to stressful condition [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some individuals might be more susceptible for the unhealthy choices due to certain psychological factors [ 44 ]. A recent study comparing students in the exam conditions versus the regular days, reported effects of stress on appetitive brain function [ 45 ]. Self-control was suggested to be affected by a personality trait which might cause overeating in susceptible subjects upon exposure to stressful condition [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing students in the exam conditions versus the regular days, reported effects of stress on appetitive brain function [ 45 ]. Self-control was suggested to be affected by a personality trait which might cause overeating in susceptible subjects upon exposure to stressful condition [ 45 ]. In addition, a recent study has reported changes in students’ dietary habits during the exams period such as decrease in diet quality, lower fruit and vegetables intake, higher fast food intake and more difficulties to eat healthy in students during the exams period [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Personality differences in stress reactivity, as measured by the behavioral inhibition scale, predicted increases in perceived stress during the final exams. Moreover, higher scores in the behavioral inhibition scale were associated with increased fMRI activity during the exam versus the nonexam period in the amygdala and ventromedial prefrontal cortex in response to foods (Neseliler et al, 2017).…”
Section: Neurobehavioral Effects Of Emotional Context On Food Processingmentioning
confidence: 95%
“…At the same times, a 100‐mm VAS was completed to assess the level of stress and relaxation felt (i.e. “How stressed (or relaxed) do you feel?”) (Fisher et al., ; Neseliler et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…"How stressed (or relaxed) do you feel?") (Fisher et al, 2016;Neseliler et al, 2017). Stunkard & Messick, 1985) were completed pre-intervention to provide additional descriptive characteristics of the sample.…”
Section: Methodsmentioning
confidence: 99%